Pengaruh Laba Akuntansi, Total Arus Kas, dan Net Profit Margin terhadap Return Saham pada Perusahaan Otomotif yang Terdaftar di Bursa Efek Indonesia - Razak, Linda A.; Syafitri, Rahmi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2018)
This study aims to determine whether accounting profit, total cash flow and Net Profit Margin effect on Return Shares in Automotive Companies listed on the Indonesia Stock Exchange. The population in this study are all automotive companies listing period 2013 - 2016. Sample taken based on certain criteria or purposive sampling. Data analysis techniques use multiple linear regression. The results show that overall from the period of 2013 to 2016 Accounting profit does not have a significant effect on stock returns due to transitory events in accounting so as not used as a reference by investors to invest, Total cash flow does not have a partial significant influence on stock return because the total cash flow is not enough to have information to be a benchmark to predict stock returns. Net profit margin has a partially significant influence on stock return because the profits generated by the company from the level of sales is also greater then it will attract investors.